The Evolution of Placentation in Flowering Plants: A Possible Role for Kin Selection - Shivaprakash, K. Nagaraju; Bawa, Kamaljit S. (Frontiers in Ecology and Evolution, 2022)
Placentation refers to the mode of ovule attachment on the wall of the ovary. In multiovulate ovaries, placentation influences interactions among developing seeds with varying degrees of kinships. Placentation is a taxonomically informative character in flowering plants, yet little has been written about the origin and evolutionary trend of various placentation types in flowering plants since Puri’s and Stebbins’ work, over six decades and almost four decades ago respectively. More recently, some authors have written about the evolution of placentation in certain groups, but an overall perspective for angiosperms is lacking. For 421 families of angiosperms, we collected data on placentation types and ovule number, and analyzed the data in the phylogenetic context using recent comprehensive phylogeny of angiosperms to test the hypotheses on the evolution of various placentation types and their association with ovule number. The distribution of placentation types across flowering plants suggests that axile placentation, followed by parietal and basal placentation, occurs more frequently across flowering plants, whereas laminar and free central placentation are very rare. Our results are more consistent with evolutionary trends proposed by Puri (1952) than by Stebbins (1974) and suggest that marginal placentation is the ancestral and most primitive placentation type, while axile is the most advanced. However, our results that marginal placentation is the ancestral and most primitive placentation type in flowering plants is at odds with early angiosperm fossil evidence. Placentation types show strong association with ovule number. Finally, our results on ovule number and placentation types support the suggestion that most angiosperms may fall into two categories: one with one or few ovule(s) and basal placentation, and another with many ovules and parietal and axile placentation. Kin selection within ovaries may play a role in explaining the observed patterns. Overall, our results provide new insights into the evolution of placentation, particularly into the drivers underlying the origin and diversification of various placentation types.